Shear Bond Strength of Two Self-Etch Adhesives to Permanent and Deciduous Dental Enamels: Effect of Acid Preconditioning - Nosrat Nourbakhsh; Maryam Khoroushi; Soha Sharif (Islamic Dental Association of Iran, 2012)
Background and Aim : There are some studies that strongly recommend acid-conditioning before applying the self-etch adhesives. The aim of this in vitro study was to compare the shear bond strength (SBS) of two self-etch adhesives to the enamel of primary and permanent teeth with acid preconditioning . Materials and Methods : The buccal surfaces of 48 permanent molars and 48 primary molar teeth were prepared for bonding of the adhesives to the enamel. Then the samples were randomly divided into eight groups, each containing 12. According to the manufacturers' instructions, Clearfil SE Bond (CSEB) and ACE All Bond SE (ABSE) self-etch adhesives were applied on the enamel and the etched enamel of both permanent and primary teeth and bonded with composite resin. After 24 hours of storage in 37˚C and 500 rounds of thermocycling, the specimens were tested in a shear at a crosshead speed of 1.0 mm/min. The results were statistically analysed using SPSS 11.5 with Kruskal-Wallis and t-test at a significance level of 0.05 . Results : The mean±SD in permanent enamels using CSEB and ABSE were 16.10±7.6 and 8.49±2.34 MPa, respectively. The same data for the deciduous enamels were 16.08±3.91 and 9.23±3.20 MPa, respectively. After acid etching, SBS for permanent enamel using CSEB and ABSE were 32.05±7.13 and 31.39±6.51 MPa, respectively. The same data for deciduous enamels were 24.73±10.74 and 21.70±6.18 MPa, respectively . Conclusion : The bond strength of CSEB was significantly higher than ABSE adhesive in both primary and permanent teeth. In addition, acid etching leads to increase in the enamel bond strength of both studied adhesives.